Rejuvenate integrated nodes through permeable spaces at Kluang Town Centre. Case study : Kluang Town Centre, Johor - Jaafar, Nur Rabiatul Adawiah (2018)
The issue about the livability in urban area has contribute to more research findings to measure the parameters livability in urban places such as city centres. As city centres well known by their great social interactions, pedestrian linkages,variety of functions and activities, Nowaday because of uncontrolled growth of cities and rapid urbanization ,vehicle domination and, also reduce the original of pedestrian life style, The city have lose the true concept and the function of city centre itself. Therefore, most of the cities become too dependent on the vehicle transportation, unutilized space, no nodes connectivity and no pedestrian linkages which led to reducing the livability of city centres in many cases . This thesis more concern on the city centres characteristics and the major aspects to evaluate the efficiency of livability of the city centre and propose a approach to create a livable and walkable city centre in study area of Kluang town centre. Therefore, connectivity and permeability are important criterion to achieve parameters of liveable cities in major scale. We can call the city as walkable and liveable city if it is well connected to major nodes, urban facilities and services. This paper first explain the methodology of research which include the literature review for better understanding the meaning of walkable and livable city centres, After that, explain the Kluang city centres evolution, and reviews references cases of walkable and livable city centre from all around the world, and next,inventory and analysis of study area to identicate the problem issue before snythesize to identify the potential area to design and suitable approach to solve the site study issue .Lastly, interprets the design on master plan within the Kluang city centre by nodes and street linkages and traffic calming approach. The liveable city is made on human interaction. Without this, the city is dead. The interaction between human depend on effective public places and effective pedestrian linkages. Hence, this study will show the important of effective urban connectivity in the urban development to achieve Kluang walkable and liveable city.